The Alliance of Sahel States against neocolonial order and the region environmental crisis (Huellas, 2025)
In 2023, the Alliance of Sahel States (AES) was established, with Burkina Faso, Niger, and the Republic of Mali as participants. These three states share certain common characteristics. They are countries with significant political, environmental, and economic vulnerabilities, yet they possess abundant mineral wealth, which is extracted by transnational corporations. The entire Sahel region is undergoing a desertification process due to high temperatures and water scarcity, further exacerbated by extractivism. Politically, all three countries face a complex mosaic of terrorist groups occupying their territories, alongside political leaders who have historically aligned with the interests of former colonial powers. Following the coups d'état in 2022, this neocolonial dynamic began to be reversed, leading to the formation of the AES, which is an alliance that aims to break neocolonial ties, boost national economies, mitigate the impacts of transnational extractivism, step up the fight against terrorism and improve the quality of life for their populations. This article aims at analyzing how the formation of the Alliance of Sahel States (AES) as a process of regional cooperation among nation-states affects the European neocolonial order regarding the extraction of natural resources in these territories and its environmental impact.